A concise review of biochar application to agricultural soils to improve soil conditions and fight pollution. (15th December 2018) - Shaaban, Muhammad; Van Zwieten, Lukas; Bashir, Saqib; Younas, Aneela; Núñez-Delgado, Avelino; Chhajro, Muhammad Afzal; Kubar, Kashif Ali; Ali, Umeed; Rana, Muhammad Shoaib; Mehmood, Mirza Abid; Hu, Ronggui
Abstract: Application of biochar to soil can play a significant role in the alteration of nutrients dynamics, soil contaminants as well as microbial functions. Therefore, strategic biochar application to soil may provide agronomic, environmental and economic benefits. Key environmental outcomes may include reduced availability of toxic metals and organic pollutants, reduced soil N losses and longer-term storage of carbon in soil. The use of biochar can certainly address key soil agronomic constraints to crop production including Al toxicity, low soil pH and may improve nutrient use efficiency. Biochar application has also demerits to soil properties and attention should be paid when using a specific biochar for a specific soil property improvement. This review provides a concise assessment and addresses impacts of biochar on soil properties. Graphical abstract: Highlights: This review provides a concise assessment of biochar impacts on soil properties. Biochar is a potential tool for the improvement of soil properties. Biochar application can address key soil agronomic constraints to crop production. Biochar can ameliorate soil pollution of a variety of pollutants. Biochar may also has demerits to soil properties.